Infrastructure mapping and strategy engagements - CGIAR Platform for Big Data in Agriculture (2019)
The effort yielded architecture diagrams that are guiding IT investment decisions in light of researcher needs and links to a unified digital strategy for CGIAR. The first concrete investment leveraging this work is a shared data analytic environment for CGIAR researchers.